Systemic intraoperative anticoagulation during arterial injury repair: Implications for patency and bleeding. Issue 4 (April 2017) - Maher, Zoё; Frank, Brian; Saillant, Noelle; Goldenberg, Anna; Dauer, Elizabeth; Hazelton, Joshua P.; Lubitz, Andrea; Zhao, Huaqing; Cannon, Jeremy W.; Seamon, Mark J.
Abstract : BACKGROUND: The role of systemic intraoperative anticoagulation (SIAC) during surgical repair of major arterial injuries is controversial. Any potential improvement in arterial patency must be weighed against the risk of hemorrhage in these critically injured patients. We hypothesized that SIAC would increase arterial patency without increasing bleeding complications. METHODS: We conducted a multi-institution, retrospective cohort study of trauma patients with major vascular injury from 2005 to 2013 in three Level I centers. Arterial injuries of the neck, torso, and proximal extremities requiring operative management were included. Our primary endpoint was maintenance of arterial patency during index hospitalization. Complications related to bleeding were assessed. The association between SIAC and arterial patency was evaluated using chi-square, t test, and multiple logistic regression modeling. RESULTS: Of 323 study patients, most were male (88%) and injured by gunshot wounds (69%). Patients repaired with SIAC (n = 154) were compared to those repaired without SIAC (n = 169). No difference in age, gender, mechanism, admission heart rate, or concomitant injury was detected between the groups (all p > 0.05). SIAC use was associated with greater arterial patency rates (93% vs. 85%, p = 0.02) without increasing return to OR for bleeding (4% vs. 6%, p = 0.29). After controlling for gender, admission hemodynamics, ISS, injury location, and postoperative anticoagulation, multivariable regression determined that SIAC patients were 2.6 times more likely (OR 2.6, 95% CI 1.1–6.2, p = 0.03) to maintain patency. Patients who maintained arterial patency were then less likely to return to the OR (9% vs. 78%, p < 0.001) with shorter intensive care unit (median 3 vs. 9 days, p < 0.01) and hospital length of stay (median 13 vs. 21 days, p < 0.01). CONCLUSION: Patients who underwent operative repair of arterial injuries utilizing SIAC experienced better arterial patency without additional bleeding complications as compared to those repaired without SIAC. Our data suggest that SIAC may improve arterial patency rates after repair and the attributable bleeding risk of SIAC may be overstated. LEVEL OF EVIDENCE: Therapeutic/care management, level IV.